Antimicrobial Action, Genotoxicity, and Morphological Analysis of Three Calcium Silicate-Based Cements - Abu Hasna, Amjad [UNESP]; Theodoro, Ana Luisa [UNESP]; Pereira, Larissa Marques [UNESP]; Ramos, Lucas de Paula [UNESP]; Campos, Tiago Moreira Bastos; Ala Rachi, Maisour; Al-Nahalwi, Talal; Oliveira, Luciane Dias de [UNESP]; Carvalho, Cláudio Antonio Talge [UNESP] (Wiley, 2022)
This study is aimed at evaluating five mineral oxides (5MO), mineral trioxide aggregate repair high plasticity (MTA HP), and mineral trioxide aggregate (MTA) in relation to the antimicrobial action over Porphyromonas gingivalis, Porphyromonas endodontalis, Parvimonas micra, Fusobacterium nucleatum, and Prevotella intermedia; the genotoxicity over mouse macrophage (RAW 264.7) and osteoblast (Mg-63) cultures; and the morphological analysis using scanning electron microscopy (SEM) analysis (50 k and ×100 k). Sodium hypochlorite (NaOCl), calcium hydroxide, and saline solution were used as control groups in the different analysis. All data were submitted to a normality test and then analyzed with one-way ANOVA, Tukey, and Kruskal-Wallis and Dunn tests, considering α≤0.05 significance level. It was found that over P. gingivalis and P. endodontalis, there was no a significant difference between the calcium silicate-based cements (CSC) and the control group of saline solution, and only 5MO was similar to the NaOCl group. However, over P. micra, all groups were effective and showed a statistically significant difference compared to the saline solution group. Conversely, none of the groups were effective over F. nucleatum and P. intermedia, except of the NaOCl group. There was a significant difference between 5MO and MTA groups in comparison with NaOCl and MTA HP over osteoblasts and macrophages after 24 hours. SEM images showed small irregular particles interspersed with some elongated needle-like particles and small irregular particles with some larger particles as well as elongated particles. It was concluded that 5MO, MTA, and MTA HP have effective antimicrobial action over P. micra. However, only 5MO is effective over P. gingivalis and P. endodontalis. Besides, 5MO and MTA are not genotoxic over mouse macrophage (RAW 264.7) and osteoblast (Mg-63) cultures.